Propagation of Prosopis Species: Problem Perseverance and Perspectives - Ramawat, K G; Nandwani, Dilip (Annals of Arid Zone, 2016)
Prosopis species are predominant components of arid-land vegetation but they are degenerated as biotic pressure has caused large scale deforesta tion. Plant tissue culture has been proved successful in regeneration of a large number of tree species. However, Prosopis species are recalcitrant to regenerate and efforts made by various workers to regenerate and propagate Prosopis are discussed in the light of achievements made in the laboratory.